2012
DOI: 10.1155/2012/812138
|View full text |Cite
|
Sign up to set email alerts
|

Screening Tests of Reproductive Immunology in Systemic Lupus Erythematosus

Abstract: Female patients in reproductive age with systemic lupus erythematosus and fertility complications together are observed by rheumatologists, gynecologists, and reproductive immunologists. The paper notes the presence of autoantibodies to zona pellucida, to phospholipids (phosphatidyl serine, phosphatidyl ethanolamine, phosphatidyl inositol, phosphatidyl glycerol, phosphatidic acid, annexin V, beta-2 glycoprotein I, and cardiolipin) and of isoantibodies to sperm cells. Isoantibodies to sperm cells are not signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…For women with lupus nephritis, kidney inflammation due to SLE, who become pregnant, the decrease in Tregs, which are needed for a successful pregnancy puts them at an increased risk for PE [6164]. SLE is also associated with antiphospholipid antibodies (aPLs) which is associated with PE, preterm birth and intrauterine growth restriction (IUGR) [65, 66]. As all of these abovementioned disorders have an underlying theme of chronic inflammation, it can be suggested that when a pathological inflammatory insult is superimposed onto the pro-inflammatory state of pregnancy, more severe complications of pregnancy, such as PE may develop [21].…”
Section: Chronic Inflammation Contributes To Endothelial Dysfunction mentioning
confidence: 99%
“…For women with lupus nephritis, kidney inflammation due to SLE, who become pregnant, the decrease in Tregs, which are needed for a successful pregnancy puts them at an increased risk for PE [6164]. SLE is also associated with antiphospholipid antibodies (aPLs) which is associated with PE, preterm birth and intrauterine growth restriction (IUGR) [65, 66]. As all of these abovementioned disorders have an underlying theme of chronic inflammation, it can be suggested that when a pathological inflammatory insult is superimposed onto the pro-inflammatory state of pregnancy, more severe complications of pregnancy, such as PE may develop [21].…”
Section: Chronic Inflammation Contributes To Endothelial Dysfunction mentioning
confidence: 99%
“…Antiphospholipid antibodies are associated with miscarriage, fetal death, intrauterine growth restriction (IUGR), preterm birth, and preeclampsia [ 33 ], and an association with recurrent miscarriage has also been reported [ 34 ].…”
Section: Antiphospholipid Antibodiesmentioning
confidence: 99%
“…Transient infertility in men with SLE may be associated with methotrexate administration and usually regresses within several months following drug discontinuation [3,[5][6][7]. Some autoantibodies, such as antiphospholipid (APL) antibodies or antisperm antibodies, may exert a significant effect on fertility [15].…”
Section: Fertility Of Patients With Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Przejściowa niepłodność u mężczyzn chorych na TRU może być związana ze stosowaniem metotreksatu i zwykle ustępuje po kilku miesiącach od odstawienia leku [3,[5][6][7]. Istotny wpływ na płodność mogą mieć niektóre autoprzeciwciała, takie jak przeciwciała antyfosfolipidowe (APL) czy przeciwciała przeciwplemnikowe [15]. …”
unclassified